2020
DOI: 10.1101/2020.04.07.029983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenic LRRK2 regulates ciliation probability upstream of Tau Tubulin kinase 2

Abstract: Mutations that activate LRRK2 protein kinase cause Parkinson's disease. We have shown previously that Rab10 phosphorylation by LRRK2 enhances its binding to RILPL1 and together, these proteins block cilia formation in a variety of cell types including patient derived iPS cells. We have used live cell fluorescence microscopy to identify, more precisely, the effect of LRRK2 kinase activity on both the formation of cilia triggered by serum starvation and loss of cilia seen upon serum re-addition. LRRK2 activity d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Pathogenic LRRK2 mutants decrease primary cilia formation in cell culture in a manner that is rescued upon LRRK2 inhibition [ 26 ]. The ability of LRRK2 to inhibit ciliogenesis requires RILPL1 binding to LRRK2-phosphorylated Rab8A and Rab10 [ 31 , 32 ]. Recent work showed that LRRK2-phosphorylated Rab proteins are dephosphorylated by a highly selective PPM1H protein phosphatase [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic LRRK2 mutants decrease primary cilia formation in cell culture in a manner that is rescued upon LRRK2 inhibition [ 26 ]. The ability of LRRK2 to inhibit ciliogenesis requires RILPL1 binding to LRRK2-phosphorylated Rab8A and Rab10 [ 31 , 32 ]. Recent work showed that LRRK2-phosphorylated Rab proteins are dephosphorylated by a highly selective PPM1H protein phosphatase [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic LRRK2 mutants decrease primary cilia formation in cell culture in a manner that is rescued upon LRRK2 inhibition [26]. The ability of LRRK2 to inhibit ciliogenesis requires RILPL1 binding to LRRK2phosphorylated Rab8A and Rab10 [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For bacterial expression, MyoVa GTD, Rab10-Q63L (1-181) and Mst3 were kind gifts from Amir Khan (Trinity College, Dublin, Ireland). mKO2-PACT was generated by amplifying the PACT domain of Pericentrin from cDNA of RPE cells as described (Sobu et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…RPE cells were transfected with Fugene HD (Promega) while A549 cells were transfected using Lipofectamine 3000 according to the manufacturer. RPE cells stably expressing mKO2-PACT were generated by lentivirus as described at (Sobu et al, 2020). Cells were checked routinely for Mycoplasma using either MycoALert Mycoplasma Detection Kit (Lonza LT07-318) or PCR.…”
Section: Methodsmentioning
confidence: 99%